Relation of Manovaha Srotas with Uterine Fibroid - Unique Case Report managed through Ayurveda (AYUSHDHARA, 2025)
In women, fibroids are often occurring benign uterine tumors, smooth muscle fibers and fibrous connective tissue make up histologically these tissues, which are also referred to as uterine leiomyomas, myomas, or fibromyomas. The development of uterine fibroids may be impacted by psychological factors. Prolonged stress possibly will encourage the development of uterine leiomyomas by influencing HPA axis, changing levels of progesterone and estrogen, triggering sympathetic nervous system, and impairing immunological function. By lowering stress and re-establishing hormonal balance, psychological treatments incidence can be lowered or may be managed. Case Description- A 27-year-old married female patient in Dept. of Striroga and Prasuti Tantra with complaints of heavy flow during menses, increased duration of menses, and painful menses. Patient was diagnosed with uterine fibroids through evaluation by ultrasound scan. Oral Formulations were prescribed based on Ayurvedic principles for correction of imbalances of dosha specifically Apana vata, and to ignite digestive fire (Agni) as well as the correction of Manovaha srotas dushti if any. Outcome- Significant relief was observed in symptoms like heavy menses and painful periods as well as improvement was seen in ultrasound scan. Conclusion- This case study illustrates how Ayurveda can effectively treat uterine fibroids.